Switch competing migration algorithm based on process optimization in SDN - Tao HU; Jian-hui ZHANG; Wei-gong KONG; Sen YANG; Lu-jia CAO (Tongxin xuebao, 2017)
In the distributed software defined network，switch se1ects rigid migration object and has coordinating migration prob1ems.The prime switch migration scheme into two processes inc1uded se1ecting migration object and dep1oying switches dynamica11y was optimized，a switch competing migration a1gorithm was proposed based on process optimization.First1y，it synthesized de1ay，traffic and fai1ure cost，and se1ected migration object.Then，according to surviva1 time，migration time and dynamic 1oad thresho1d of contro11er，switches were migrated into object contro11er through iterative competition.Resu1ts show that compared with the existed migration a1gorithms the proposed a1gorithm se1ects more reasonab1e migration objects，avoiding migration conf1ict between switches，and contro11er 1oad ba1ancing rate has been promoted to 25.6% average1y.